Radiative Peristaltic Flow of Jeffrey Nanofluid with Slip Conditions and Joule Heating. - Tasawar Hayat; Maryam Shafique; Anum Tanveer; Ahmed Alsaedi (PLoS ONE, 2016)
Mixed convection peristaltic flow of Jeffrey nanofluid in a channel with compliant walls is addressed here. The present investigation includes the viscous dissipation, thermal radiation and Joule heating. Whole analysis is performed for velocity, thermal and concentration slip conditions. Related problems through long wavelength and low Reynolds number are examined for stream function, temperature and concentration. Impacts of thermal radiation, Hartman number, Brownian motion parameter, thermophoresis, Joule heating and slip parameters are explored in detail. Clearly temperature is a decreasing function of Hartman number and radiation parameter.